Integration of non-energy among the end-use demands of bottom-up whole-energy system models - Rixhon, Xavier; Tonelli, Davide; Colla, Martin; Verleysen, Kevin; Limpens, Gauthier; Jeanmart, Hervé; Contino, Francesco (Frontiers in Energy Research, 2022)
The complexity of bottom-up energy system models has progressively grown. Among them, whole-energy system models aim at representing the energy resources, conversion technologies and energy demand of regions (i.e., a country) in its entirety. Despite this effort leading to an increased number of conversion processes modelled, the typologies of end-use demand have remained limited to three categories: electricity, heat and transportation. A fourth category, herein addressed as non-energy demand, has widely been neglected. Being associated as the feedstock in the production of chemicals (i.e., plastics and fertilizers), the non-energy demand represents 10% of the world total end-use demand. Its relevance becomes fundamental in analyses which define the optimal defossilisation pathways of energy systems at high dependence from fossil resources. This contribution introduces a schematic representation of the conversion processes involved in the satisfaction of the non-energy demand. Through its implementation in a bottom-up whole-energy system model, it evaluates the impact of this additional end-use in the configuration of the optimal energy system. The Belgian energy system, characterised by a penetration of the chemical and the petrochemical industries up to 20% of its total end-use demand, is taken as reference case. The transition to a defossilised energy system is enforced through a snapshot analysis with a progressively more restrictive emissions cap. The results emphasize the role of renewable carriers (i.e., methanol and ammonia), otherwise hindered when the non-energy demand is neglected. The 100% import of these carriers at the lowest emissions cap highlights the potential dependence of the country under analysis, with limited availability of renewable resources, from countries exporting renewable methanol and ammonia.